Insight into the reversible structural crystalline-state transformation from MIL-53(Al) to MIL-68(Al). Issue 4 (8th January 2018) - Perea-Cachero, Adelaida; Romero, Enrique; Téllez, Carlos; Coronas, Joaquín
Abstract : The reversible crystalline transformation from MIL-53(Al) into MIL-68(Al) was accomplished. Abstract : The reversible crystalline transformation between MIL-53(Al) and MIL-68(Al) is described. This followed a uniform conversion model with cleavage and formation of metal–ligand bonds after exchange or removal of guest molecules. MIL-68(Al) materials produced during the transformations had higher thermal stability and crystallinity than the as-synthesized MIL-68(Al).